2021
DOI: 10.2147/dmso.s325115
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Body Composition and Lifestyle in Chinese University Students with Normal-Weight Obesity: A Cross-Sectional Study

Abstract: Normal weight obesity (NWO), defined as normal body mass index (BMI) and excessive body fat percentage (BF%), has been shown to be associated with a significantly higher risk of developing metabolic syndrome, cardiometabolic dysfunction and with higher mortality. However, there is limited literature regarding the potential associations between NWO and lifestyles. This study aimed to investigate the associations of lifestyles with NWO in Chinese university students. Participants and Methods: A total of 279 univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…This was consistent with the previous results of overweight/obesity and body fat distribution. The same conclusion could be found in other research [ 47 , 48 , 49 ], which showed that high dietary quality in adolescents can improve nutrient status and be associated with a lower percentage of body mass. Samanta T. Valdés [ 45 ] reported that overweight individuals were more predisposed to vitamin deficiency, due to differences in the intake of dietary fruit, vegetables, and energy by individuals with overweight and obesity as compared to individuals of normal weight.…”
Section: Discussionsupporting
confidence: 89%
“…This was consistent with the previous results of overweight/obesity and body fat distribution. The same conclusion could be found in other research [ 47 , 48 , 49 ], which showed that high dietary quality in adolescents can improve nutrient status and be associated with a lower percentage of body mass. Samanta T. Valdés [ 45 ] reported that overweight individuals were more predisposed to vitamin deficiency, due to differences in the intake of dietary fruit, vegetables, and energy by individuals with overweight and obesity as compared to individuals of normal weight.…”
Section: Discussionsupporting
confidence: 89%
“…One study demonstrated that individuals with NWO have similar diet quality scores but lower physical fitness levels than lean individuals and, thus, a higher quality of diet than those who are overweight or suffer from obesity ( 81 ). Physical exercise prevents the development of an NWO phenotype ( 82 ). A program of resistance exercise combined with a dairy supplement significantly decreases FM and improves the metabolic parameters better than a standard supplement in overweight individuals with low MM ( 83 ).…”
Section: Dietary Physical Exercise and Pharmacological Treatments Tai...mentioning
confidence: 99%
“…Accordingly, the maximum score for item 27 was 1 (a power analysis was conducted) instead of 5 and thus the highest possible score for studies in this review was 28 (instead of 32). The modified Downs and Black score ranges were given corresponding quality levels as previously reported [47,48]: excellent (26)(27)(28); good (20)(21)(22)(23)(24)(25); fair (15)(16)(17)(18)(19); and poor (≤14). Any discrepancies between reviewers were resolved through discussion until consensus was reached, if a consensus could not be reached, a third reviewer (CP) was consulted.…”
Section: Study Quality and Risk Of Biasmentioning
confidence: 99%
“…Compared to university students who are more active, those who are less active have an increased chance of obesity [16][17][18] and its associated metabolic risk factors [19,20]. This period of early adulthood can be a critical time for the development of obesity as an increased body mass index (BMI) during this time is associated with higher morbidity, premature mortality, and chronic obesity [21].…”
Section: Introductionmentioning
confidence: 99%